2011
DOI: 10.1161/circinterventions.110.957548
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polymer Formulations on Neointimal Proliferation After Zotarolimus-Eluting Stent With Different Polymers

Abstract: Background— Polymer formulation may affect the efficacy of drug-eluting stents. Resolute, Endeavor, and ZoMaxx are zotarolimus-eluting stents with different stent platforms and different polymer coatings and have been tested in clinical trials. The aim of this analysis was to compare the efficacy of zotarolimus-eluting stents with different polymers. Methods and Results— Data were obtained from the first-in man trial or first randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Taken together with the recent observation from the Resolute‐US trial investigators , this study suggest that the adoption of the novel R‐ZES in the clinical practice may translate into improved clinical outcomes compared to that associated with the E‐ZES. Such findings fit with the lower neointimal growth in R‐ZES compared to E‐ZES documented by intravascular ultrasound thus reinforcing the perception that polymer‐coating is key modulator of the DES clinical performance.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Taken together with the recent observation from the Resolute‐US trial investigators , this study suggest that the adoption of the novel R‐ZES in the clinical practice may translate into improved clinical outcomes compared to that associated with the E‐ZES. Such findings fit with the lower neointimal growth in R‐ZES compared to E‐ZES documented by intravascular ultrasound thus reinforcing the perception that polymer‐coating is key modulator of the DES clinical performance.…”
Section: Discussionsupporting
confidence: 77%
“…Then, a novel zotarolimus‐eluting stent (Resolute Zotarolimus‐eluting stent, R‐ZES) (Medtronic, Santa Rosa, California), differing from E‐ZES in the polymer coating only, became available . Experimental studies have shown that the new polymer system is associated to better biocompatibility, less inflammation, and extended drug‐elution kinetics .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, endothelial dysfunction as well as pro-inflammatory characteristics of MetS could be factors governing local pharmacokinetics, and thus these characteristics of MetS might differently affect the clinical outcomes between EES and R-ZES, which have different drug-release kinetics and stent structures [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, thinner stent struts favor a better and homogeneous endothelial strut coverage as compared to the thicker stainless steel struts of the first‐generation DES, and DES with thin struts have shown a low risk of adverse cardiovascular events in patients with a variety of clinical syndromes . The R‐ZES uses a biocompatible durable polymer that enables longer drug elution and has shown to significantly affect the amount of neointima compared with the previous zotarolimus‐eluting platform . Moreover, OCT studies have demonstrated essentially complete endothelial coverage at 3 months with this device …”
Section: Discussionmentioning
confidence: 99%